Directory of nearest hospitals using mobile service - Mouri, Farzana Islam; Shabbin, Tasnuva (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.